The Impact of Starvation on the Microbiome and Gut-Brain Interaction in Anorexia Nervosa - Seitz, Jochen; Belheouane, Meriem; Schulz, Nina; Dempfle, Astrid; Baines, John F.; Herpertz-Dahlmann, Beate (Frontiers in Endocrinology, 2019)
Interactions between the gut microbiome and the brain are of increasing interest to both researchers and clinicians. Evidence is mounting on the causal role of an altered gut microbiome in inflammatory diseases such as arthritis, inflammatory bowel disease, obesity and diabetes, and psychiatric diseases like anxiety and depression. Mechanisms include altered energy harvest from food, hormonal changes, increased gut permeability, inflammation, immune response and a direct influence on the brain and behavior. Anorexia nervosa (AN) is the third most common disease in adolescence and exacts a high burden on patients and caregivers. It often becomes chronic and has the highest mortality of all psychiatric diseases. As AN is characterized by nutritional restrictions, weight loss, and severe behavioral symptoms including weight phobia, comorbid anxiety and depression, accompanied by endocrine alterations, increased inflammation and immune response, exploring the role of the gut microbiome is crucial. Here, we present an overview of the potential mechanisms of interaction between the gut microbiome, the host and particularly the brain in AN and summarize the initial findings of microbiome research on AN. We conclude by identifying future research directions and potential therapeutic approaches, including nutritional interventions, probiotics, prebiotics and food supplements, that could become important additions to current AN therapy.